Penerapan Metode VIKOR Pada Pengambilan Keputusan Seleksi Calon Penerima Beasiswa di SMK TPI Al-Hassanah Pematang Bandar - Desi Ayu Ningsih; Dedy Hartama; Rafiqa Dewi (LPPM STIKOM Tunas Bangsa, 2020)
The purpose of this research is to build a decision support system that can be used by schools in the selection of scholarship recipients, which requires completion, as decision support with multicriteria is the VIKOR method. The basic concept of the VIKOR method is to determine the ranking of the existing samples. This study aims to apply the VIKOR method to the selection of scholarship recipients that can be used to assist the student section in determining the recommendation for scholarship acceptance at SMK TPI AL-HASANNAH Pematang Bandar by considering various predetermined criteria. The criteria used in this study are value, parent's income, parent's dependents, number of siblings. The results show that the VIKOR method can be used to assist the selection process and determine the right scholarship recipient. In the VIKOR method, each weight given shows the same results, so that it can be used as a compromise solution in dealing with multicriteria problems.